Ranitidine reversed the hyperaemic response in the stomach of rats exposed to immobilization stress - M.K. Shindala; S.M. A. AL-Nuimi (University of Mosul, 2005)
The immobilization stress has been recently recognized to produce marked increase of gastric acid secretion and cause hyperaemia in the stomach . Since ranitidine reduced corpus mucosal blood flow in the stomach to basal levels, it may cause suppression of hyperaemia induced by immobilization stress. In this study, 5 groups of 5 rats each were used. The extent of hyperaemia in the glandular mucosa of the stomach of control rats (pretreated with saline) exposed to stress was compared with ranitidine treatment 30 minutes before onset of stress. Gastric hyperaemia elicited in the control rats, while treatment with ranitidine (20 and 40 mg/kg i.m.) 30 minutes before onset of stress, caused a dose - dependent reduction in the gastric hyperaemia response to stress. Furthermore, pretreatment with ranitidine in different doses did not suppress the increase in alanine amino transferase (ALT) activity induced by stress as well as there was no significant difference between plasma cholesterol level in all investigated groups. In conclusion, the present study demonstrates that gastric damage produced by immobilization stress can be protected by ranitidine.